1999
DOI: 10.1007/bf03013953
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular tenoxicam improves postoperative analgesia in knee arthroscopy

Abstract: Intra-articular tenoxicam improves postoperative analgesia in knee arthroscopyPurpose: Non Steroidal Anti-Inflammatory drugs have a well documented benef~ in the relief of postoperative pain. This study was designed to compare the analgesic effect of intra-articular tenoxicam 20 mg with intravenous tenoxicam on postoperative pain in 88 patients undergoing day case knee arthroscopy. Methods: A prospective, double blind, randomized trial was performed. All patients received a standard general anesthetic. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…An ideal agent should be active on cessation of surgery, have a prolonged duration of action, be easy to administer and have no serious side effects 4 .…”
Section: Discussionmentioning
confidence: 99%
“…An ideal agent should be active on cessation of surgery, have a prolonged duration of action, be easy to administer and have no serious side effects 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The third drug we administered is tenoxicam, a NSAID which has been used in studies intraarticularly, alone or in combination with local anaesthetics [8][9][10][11][12][13]. It has been shown that i.a tenoxicam provided superior postoperative analgesia and reduced analgesic requirements compared to intravenous tenoxicam indicating a peripheral analgesic effect [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…333 Tenoxicam, 20 mg, has been used successfully both as a sole intra-articular analgesic and as an adjunct in combination therapy. 334,335 …”
Section: Intra-articular Nsaidsmentioning
confidence: 98%